Catalyst performance and experimental validation of a rigorous desorber model for low temperature catalyst-aided desorption of CO2 in single and blended amine solutions. Issue 4 (August 2017) - Decardi-Nelson, Benjamin; Akachuku, Ananda; Osei, Priscilla; Srisang, Wayuta; Pouryousefi, Fatemeh; Idem, Raphael
Highlights: Results show the catalyst-aided desorption of CO2 in a CO2 capture pilot plant. A model developed predicts CO2 production rates with Absolute Average Deviation (AAD) of 7.7%. The new model also predicts the temperature profiles in the desorption column. HZSM-5 performs better than γ-Al2 O3 in both single and blended amine solutions. The model was used to show a high CO2 concentration profile in the modified desorber. Abstract: In this study, experimental results of an integrated CO2 capture pilot plant utilizing blended MEA-MDEA solution and two solid acid catalysts (γ-Al2 O3 and HZSM-5) in the desorber are presented, and a model developed in-house was validated against the experimental data. The model showed good agreement with the pilot plant data with an absolute average deviation (AAD) of 7.7% for CO2 production rates and could predict well the temperature profiles in the column. The model which has been previously validated against experimental data utilizing MEA and the two solid acid catalysts, was used to predict the performance (in terms of their contribution to the overall reaction rates) of the solid acid catalysts in both solvents (single and blended amine solutions). The performance results showed that the catalysts contributed more to the process as the temperature and amount of catalyst increased with HZSM-5 yielding as high as 95% increase to the overall rate of reaction in the single amine system. The results of the performance of the catalysts in the blended solvent were quite low compared to those of the single amine solution. It was observed that the predicted gas phase CO2 concentration profiles in the desorber, which was not readily available experimentally, was quite high and undesired. Thus, further steps should be taken to address this problem.